Improved Processing of Poultry Litter Reduces Nitrate Leaching and Enhances Its Fertilizer Quality - Chaudhry, A.N.; Jilani, G.; Khan, M.A.; Iqbal, T. (Asian Journal of Chemistry, 2010)
Improper storage, handling and land application of poultry litter result in environmental pollution and loss of plant nutrients. Processing it in a suitable manner will assure the availability of plants nutrients, prevent water contamination and destruction of pathogens. This study was meant to employ different field conditions and new techniques viz., shade, cover, open-air, dumping and concrete-bed, for judicious handling of poultry litter waste. These techniques were compared for both natural as well as composting situation under a three factor factorial design. Data were collected on leaching of NO3-N, decomposition pattern, nutrients contribution to farmland and yield of wheat. Results revealed that nitrate leaching was maximum (16.6 μg g-1) with dump storage followed by open-air storage (14.9 μg g-1). Over time, leached nitrate concentration in soil also increased being maximum after 90 d (15.7 μg g-1) with natural storage. Moreover, soils under poultry litter stock varied significantly for their NO3 concentration under natural and composting condition. Land application of composted poultry litter gave significantly higher wheat yield as compared to naturally stocked poultry litter. Covered condition was found advanta-geous over open-air and under-shade processing of poultry litter with respect to fertilizer value for wheat production.